Barriers and facilitators affecting course completions by apprentices and trainees with disabilities - Cocks, Errol; Thoresen, Stian (NCVER, 2013)
Apprenticeships and traineeships are useful pathways for people with a disability to obtain a qualification and gain employment. Based on a three-year program of research, this report explores the barriers and facilitators of course completion reported by students with a disability who have completed an apprenticeship or traineeship. Formal and informal support was the greatest facilitator to completion, and lack of resources the major barrier. This included poor training wages, equipment costs and a lack of time, often due to family commitments.